Faktor yang Mempengaruhi Rendahnya Peserta Didik di SDN Blu’uran 2 Kecamatan Karang Penang, Kabupaten Sampang - Sinnatul Ula, Anisa; Aprilia, Rika; Sephia Anisati, Ananda (JOURNAL OF EDUCATION FOR ALL, 2023)
This study aims to analyze the factors in student management that affect the low number of students at SDN Blu'uran 2. The method used is a qualitative approach with a qualitative descriptive method. Data collection techniques consist of three ways, namely observation, interviews, and documentation studies. Data management techniques use qualitative analysis techniques which consist of three stages, namely data reduction, data presentation, and drawing conclusions. The results showed that the management of students at SDN Blu'uran 2 was not optimal and did not work well. This is supported by internal factors, namely the lack of teaching staff and adequate infrastructure and external factors, namely the location of educational institutions close to Islamic-based private educational institutions.